2006
DOI: 10.1111/j.1365-2257.2006.00823.x
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of haematological diseases diagnosed by bone marrow examination in Yemen: a developing country experience

Abstract: There is lack of information about the relative prevalence of haematological disorders in Yemen and other Middle East countries. The aim of this study was to evaluate the pattern of haematological diseases diagnosed by bone marrow examination in Yemen considering the limited diagnostic facilities. At the referral haematology centre in Yemen, between November 1999 and November 2005, 785 patients >14 years old were evaluated by bone marrow examination. Relevant investigations were performed when needed. A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
12
3
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 17 publications
(19 reference statements)
8
12
3
1
Order By: Relevance
“…The fact that we got more cases of AML than CML in our study may be explained by the fact that Bone Marrow Examination was the basis of case collection in our study and some cases of CML diagnosed only on peripheral smear might have been missed. Studies of Idris M et al [7] and Al Ghazaly et al [2] match our fi ndings of AML being the most common form among all leukemias.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The fact that we got more cases of AML than CML in our study may be explained by the fact that Bone Marrow Examination was the basis of case collection in our study and some cases of CML diagnosed only on peripheral smear might have been missed. Studies of Idris M et al [7] and Al Ghazaly et al [2] match our fi ndings of AML being the most common form among all leukemias.…”
Section: Discussionsupporting
confidence: 91%
“…Leukemias We found a very high distribution of acute leukemias -92 / 129 (71%) cases of leukemias compared to 123 chronic leukemia 37/129 (28.5%). Similar high incidence of Acute leukemia has been reported by Kwiatkowski A [6], C Besson et al [3], Idris M [7], Al Ghazaly et al [2], Pradhan PK et al [8] and Chatterjea et al [9]. However Hansen NE et al [10] found more cases of chronic leukemias in their study (60%) as compared to acute leukemias.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Hematological parameters in our study were as follows: (11) Al-Ghazaly J et al (2006) (12) Our study (2009)(2010)(2011)(2012) Our findings are similar to others as majority of cases were in nonmalignant group and most common disease in nonmalignant group was megaloblastic anemia, Anita et al 11 reported 87% MA unusually high, reason may be, she has studied all cases having anemia. In our series MA incidence is much higher 41.81% in comparison to 12.3% Pudasaini et al 9 study in Nepal & 24.92% reported by Fazlur Rahman et al 10, Pakistan, both are different geographically and in food behavior.…”
Section: Snosupporting
confidence: 82%
“…Our study is in concordance with the various other studies from developing countries which reflect high prevalence of nutritional anemias (megaloblastic anemia, iron deÞ ciency and mixed deÞ ciency) among non pediatric population. [2,3] Organomegaly was present in a lower percentage of our cases as compared with Sarode et al [4] Co-existing iron deÞ ciency (mixed deÞ ciency) …”
Section: Letters To Editor Spectrum and Analysis Of Bone Marrow Findimentioning
confidence: 44%